66.067 Kimyo va kimyoviy texnologiyalar: CLEANING OF SATURATED ABSORBENTS USED IN NATURAL GAS CLEANING BY THREE-STAGE FILTRATION METHOD AND ANALYSIS OF THEIR PROPERTIES - Turayev , Tolib; Bozorova, Gavhar; Eshankulov, Nurbek; Kadirov, Khasan; Dushamov , Alimbay; Murtozoeva, Shodiya (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article presents the results of research on the purification of aqueous solutions of used-saturated ethanolamines from toxic compounds by a three-stage filtration method. In the study, the purification process of ethanolamines by three-stage filtration (sand, charcoal - bentonite and anionite (Tulsion (USA) A-23 and AV-17-8 of the Russian Federation strong base gel type anionites)) was studied, it was found to be the most effective method, and their properties were analyzed done.